Concept Mapping in Simulation within Nursing Education: A Scoping Review Protocol - Jennifer Innis; Sarah Johnston; Erica Cambly (MDPI AG, 2023)
Background: Simulation has been found to enhance nursing student knowledge and confidence, as well as to improve clinical performance. The use of concept maps during simulation has been found to play a key role in student learning. There is a need to understand what is known to date about the use of concept mapping in simulation within nursing education. This will help determine the most effective ways to use concept mapping in simulation to foster learning in nursing students. Scoping review question: What is known about the context, processes, and outcomes of concept mapping in simulation within nursing education? Methods: The scoping review will be conducted in accordance with JBI methodology for scoping reviews and will search the following databases: MEDLINE, CINAHL, PsycMED, EMBASE, and ERIC. This review will consider studies that explore the use of concept mapping in simulation within undergraduate nursing education and will include studies that have used qualitative, quantitative, and mixed methods, as well as literature reviews. Editorials, commentaries, and gray literature will be excluded. Studies published from 1992 onward will be included. The data extracted will include details about the participants, how concept mapping was used within simulation, methods, key findings, and research gaps.